A non-native fish species reaches the south-western European waters: the Atlantic croaker, Micropogonias undulatus (Acanthuriformes, Sciaenidae) and its invasion history in Europe - Carvalho-Souza, G. F.; Lobato, Cristóbal; González-Ortegón, Enrique (Biodiversity Data Journal, 2024)
© 2024 Gustavo de Carvalho-Souza, Cristóbal Gómez, Enrique González-Ortegón. This is an open access article distributed under the terms of the Creative Commons Attribution License (CC BY 4.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. The Atlantic croaker Micropogonias undulatus, a sciaenid fish native to the North Atlantic American coast, holds importance in recreational and commercial fisheries. Moreover, its potential as an invasive species should be noted, given its expansion and establishment in Atlantic European waters. This study reports its southernmost occurrence in Europe, in the Gulf of Cadiz. Morphological and molecular analysis confirmed its identity, revealing genetic similarities to US sequences. A comprehensive review of historical non-native distribution records underscored the species' expansion throughout European waters, suggesting human-mediated introduction. The escalating frequency of such arrivals emphasises the critical need for effective monitoring and management efforts in order to control non-native species in this region. GF de C-S acknowledges support from the Spanish Ministry of Universities for the Margarita Salas Postdoctoral Fellowship funded through the Next Generation EU programme (UCA/R155REC/2021) and Spanish State Research Agency (PTA2022-021378-I). Peer reviewed